The Relationship between Servant Leadership Practices and Employee Job Satisfaction in Public Organizations in Tanzania - Limo, Herrieth C; Malipula, Mrisho M; Yusuph, Rashid R (UI Scholars Hub, 2024)
This study assesses the relationship between servant leadership practices and job satisfaction in public organizations in Tanzania, with a focus on Posts Corporation Headquarters (TPCH). It employed a descriptive survey and correlational design involving 150 respondents. Quantitative data were analyzed using the statistical program IBM SPSS Statistics 25, while qualitative data were examined using content analysis. The findings indicate that servant leadership has been thoroughly practiced at TPCH, as indicated by a mean score of 3.63 and a standard deviation of 0.943. The relationship between characteristics of servant leadership and job satisfaction is highly significant and positive (rp values ranging from 0.62 to 0.69, p 0.001). Regression analysis establishes that servant leadership strongly predicts employee job satisfaction (B=0.694, t=6.722, p 0.000). The study further reveals key factors of servant leadership contributing to improved job satisfaction, including leaders leveraging their positions for the good of their subordinates, providing support and affirmation, sharing organizational plans and objectives, demonstrating openness in listening, and prioritizing employee needs. Therefore, the study recommends that TPCH leadership and stakeholders work assiduously to strengthen a culture of servant leadership to sustain and improve job satisfaction.